High‐Density and Thermally Stable Palladium Single‐Atom Catalysts for Chemoselective Hydrogenations. (17th September 2020) - Ma, Ying; Ren, Yujing; Zhou, Yanan; Liu, Wei; Baaziz, Walid; Ersen, Ovidiu; Pham‐Huu, Cuong; Greiner, Mark; Chu, Wei; Wang, Aiqin; Zhang, Tao; Liu, Yuefeng
Abstract: Single‐atom catalysts (SACs) have shown superior activity and/or selectivity for many energy‐ and environment‐related reactions, but their stability at high site density and under reducing atmosphere remains unresolved. Herein, we elucidate the intrinsic driving force of a Pd single atom with high site density (up to 5 wt %) under reducing atmosphere, and its unique catalytic performance for hydrogenation reactions. In situ experiments and calculations reveal that Pd atoms tend to migrate into the surface vacancy‐enriched MoC surface during the carburization process by transferring oxide crystals to carbide crystals, leading to the surface enrichment of atomic Pd instead of formation of particles. The Pd1 /α‐MoC catalyst exhibits high activity and excellent selectivity for liquid‐phase hydrogenation of substituted nitroaromatics (>99 %) and gas‐phase hydrogenation of CO2 to CO (>98 %). The Pd1 /α‐MoC catalyst could endure up to 400 °C without any observable aggregation of single atoms. Abstract : A Pd1 /α‐MoC catalyst with high mass loading could endure harsh reducing/reacting atmosphere up to 400 °C without any observable aggregation of single atoms. A pathway is thus provided to decouple the hydrogenation activity and stability of single‐atom catalysts.